1994
DOI: 10.1089/jam.1994.7.345
|View full text |Cite
|
Sign up to set email alerts
|

Nebulizer Therapy with Antibiotics in Chronic Suppurative Lung Disease

Abstract: Aerosolized antibiotics have been shown to be a useful modality of treatment in patients with cystic fibrosis. In this investigation we examined the utility of this treatment in patients with other chronic suppurative lung disorders. These included forty patients, thirty men and ten women with chronic airway infection (27 with bronchiectasis, 6 with chronic abscess and 7 with chronic suppurative bronchitis). Pathogenic organisms were isolated from the affected part of the lung by a fiberoptic bronchoscopy usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Sputum volume in 24 h is a potentially useful marker as it is highly pertinent to the condition, noninvasive, easily accessible and inexpensive. It has been used as a marker in previous studies that have assessed potential long-term therapeutic strategies including inhaled steroids and long-term antibiotics [16][17][18][19][20][21]. A recent study has shown wet weight sputum to be as reliable as dry sputum [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sputum volume in 24 h is a potentially useful marker as it is highly pertinent to the condition, noninvasive, easily accessible and inexpensive. It has been used as a marker in previous studies that have assessed potential long-term therapeutic strategies including inhaled steroids and long-term antibiotics [16][17][18][19][20][21]. A recent study has shown wet weight sputum to be as reliable as dry sputum [22].…”
Section: Discussionmentioning
confidence: 99%
“…One study examining changes in lung function after intravenous antibiotic therapy found an increase in FEV 1 but no change in FVC,371 while increases in PEF, FEV 1 and FVC were seen in another 369. Lung function testing is an important aspect of assessing tolerability of nebulised antibiotics (Appendix 1) and can detect improvement after nebulised antibiotics 369.…”
Section: Section 3: Clinical Assessment and Investigationsmentioning
confidence: 99%
“…Lung function testing is an important aspect of assessing tolerability of nebulised antibiotics (Appendix 1) and can detect improvement after nebulised antibiotics 369. Patients with PCD show stabilisation of lung function when managed aggressively with repeated spirometry and antibiotics 179…”
Section: Section 3: Clinical Assessment and Investigationsmentioning
confidence: 99%
See 2 more Smart Citations